Hybrid layer-by-layer (LbL) films of polyaniline, graphene oxide and zinc oxide to detect ammonia - Andre, Rafaela S.; Shimizu, Flávio M.; Miyazaki, Celina M.; Riul, Antonio; Manzani, Danilo [UNESP]; Ribeiro, Sidney J.L. [UNESP]; Oliveira, Osvaldo N.; Mattoso, Luiz H.C.; Correa, Daniel S. (Elsevier, 2017)
Reliable gas sensors operating at room temperature are in demand for monitoring the environment for hazardous pollutants, such as ammonia (NH3) gas that may become toxic to humans and animals above a threshold concentration. In this paper we report on the combination of three materials, namely polyaniline (PANI), graphene oxide (GO) and zinc oxide (ZnO), to produce hybrid layer-by-layer (LbL) films used for sensing NH3 with impedance spectroscopy measurements. The deposition of tetralayered PANI/GO/PANI/ZnO LbL films was confirmed with UV–vis. absorption and Raman spectroscopies, while atomic force microscopy (AFM) served to investigate film morphology. Exposure of these LbL films to NH3 caused film roughness to vary, in an effect that depended on the number of tetralayers. Because of synergy in the materials properties, the films with 3 tetralayers were found to be the most adequate for detecting NH3 in the range from 25 ppm to 500 ppm with a response time of 30 s. These figures of merit are adequate for monitoring working environments regarding gas exposure, and highlight the usefulness of the control of film architecture provided by the LbL technique.
Keywords: Ammonia sensor; Graphene oxide; Impedance spectroscopy; Nanostructured film; Polyaniline